2018
DOI: 10.1038/bjc.2017.461
|View full text |Cite
|
Sign up to set email alerts
|

H1/pHGFK1 nanoparticles exert anti-tumoural and radiosensitising effects by inhibition of MET in glioblastoma

Abstract: H1/pHGFK1 exerts anti-tumoural and radiosensitive activities mainly through the inhibition and reversal of IR-induced MET and ATM-Chk2 axis activities in glioblastoma. H1/pHGFK1 nanoparticles are a potential radiosensitiser and angiogenic inhibitor for glioblastoma treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 43 publications
0
31
0
Order By: Relevance
“…Compared with conventional live or subunit vaccines, DNA vaccines are easy to manufacture, are highly stable, and generally present fewer safety concerns than other types of vaccines (10). H1 nanoparticles have been applied to a safe system for DNA delivery (28). AIM2 is a host protein and vaccination with H1-pAIM2/pCAIX vaccine might have inflammation risk.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Compared with conventional live or subunit vaccines, DNA vaccines are easy to manufacture, are highly stable, and generally present fewer safety concerns than other types of vaccines (10). H1 nanoparticles have been applied to a safe system for DNA delivery (28). AIM2 is a host protein and vaccination with H1-pAIM2/pCAIX vaccine might have inflammation risk.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown significant success using H1 nanoparticle-based delivery system to deliver genes in mice. This delivery system also did not show elevated inflammation in serum or a nonspecific immune response in vivo, suggesting its low toxicity (27,28). Therefore, H1 nanoparticlebased delivery system may enhance the therapeutic effect of DNA vaccine for tumor treatment.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Our previous study has demonstrated that H1 nanoparticles were an effective delivery system for gene expression in vitro and in vivo. 26 Thus, H1/pAIM2 or control nanoparticles were prepared (Figure 2A) and transiently transfected into 786-O or OSRC-2 cells. The result showed AIM2 expression was significantly increased in both renal cancer cell lines as compared with control ( Figure 2B).…”
Section: H1/aim2 Inhibited Renal Cancer Cell Proliferation and Prommentioning
confidence: 99%
“…Folate‐grafted PEI600‐CyD (H1) as a non‐viral gene delivery vehicle can effectively condense plasmid DNA to form stable functionalized nanoparticles . Recent studies have shown a significant success using H1 to deliver genes in vivo . More importantly, H1‐based delivery system leads to neither elevate enzymes in serum nor a non‐specific immune response in mice, suggesting its low toxicity .…”
Section: Introductionmentioning
confidence: 99%